MANAJEMEN STRATEGI UNTUK MENINGKATKAN PENJUALAN FOOD AND BEVERAGE DI ERA PANDEMI COVID 19 - Septiningrum, Liana Dwi (FEB Universitas Sam Ratulangi Manado, 2021)
Abstract: The purpose of this study was to determine the management strategy in the form of planning, implementation, coordination and evaluation in increasing benefit in food and beverage sector during the Covid 19 pandemic era. This research method is descriptive qualitative. The population is all businesses in the food and beverage sector in South Tangerang, and the sample used is purposive sampling, namely the PIRO restaurant. Data collection techniques with in-depth interviews with CEOs and Founders, Supervisors and Employees. The data analysis technique used source triangulation. The results of the research include planning by making a sales framework that prioritizes customer service, increasing product innovation, and improving marketing strategies. For implementation by serving food quickly without reducing quality, providing a comfortable place and space for consumers and innovating in adding new menus. In coordination, namely controlling and improving employee performance to maintain SOP, and controlling the quality of taste in the menu. Evaluation in this case by giving regular questionnaires to consumers on service and menu quality, giving rewards and punishments to employees.Â Abstrak: Tujuan dari penelitian ini adalah untuk mengetahui manajemen strategi berupa perencanaan, pelaksanaan, pengkoordinasi dan evaluasi dalam meningkatkan penjualan di bidang food and beverage pada era pandemic COVID19. Metode penelitian ini adalah kualitatif deskriptif. Dengan populasi adalah seluruh usaha bidang food and beverage dalam tangerang selatan, dan sampel yang digunakan adalah purposive sampling yaitu restaurant PIRO. Teknik pengumpulan data dengan wawancara mendalam CEO dan Founder, Supervisor dan Tenaga Karyawan. Teknik analisis data menggunakan triangulasi sumber. Hasil dari penelitian meliputi, perencanaan dengan membuat kerangka penjualan mengutamakan pelayanan konsumen, peningkatan inovasi produk, dan meningkatkan strategi pemasaran. Untuk pelaksanaan dengan menyajikan makanan dengan cepat tanpa mengurangi kualitas, memberikan tempat dan ruangan yang nyaman untuk konsumen dan berinovasi pada penambahan menu baru. Dalam pengkoordinasian yaitu mengontrol dan meningkatkan kinerja karyawan untuk tetap memegang SOP, dan mengontrol kualitas rasa dalam menu. Evaluasi dalam hal ini dengan memberikan kuesioner rutin pada konsumen dalam layanan dan kualitas menu, memberikan reward and punishment pada karyawan.